Le musée Bourdelle, lieu de mémoire et de valorisation d’une collection monographique - Chloë Théault (In Situ)
Antoine Bourdelle already had the idea for a museum dedicated to his work as early as 1922, but this museum only opened 20 years after his death, in 1949. It was first located in the former studios of the artist, dating from the nineteenth century, and was then completed by new exhibition rooms: a monumental hall in 1961 and an extension designed by the architect Christian de Portzamparc in 1992. This article looks at some of the important milestones in the creation of the museum and at the sources of inspiration embodied in its architecture. It also examines how Bourdelle’s works of art, mainly bronzes and plasters, are exhibited and interact with the different rooms of the museum, which mingle various identities and periods.